Vitamin D3 Deficiency is a risk Factor for the Low Ferritin in Iraqi Alzheimer’s type-2- Diabetic Patients - Jasim, Rasha Zuhair; Yassen, Samira; Sarah Abdullah Hamad (ASJ - Academic Science Journal, 2026)
Alzheimer’s disease and Type-2- Diabetes Mellitus are prevalent chronic diseases linked by likely a bi-directional relationship, this relationship is partially understood. the aim of the present study is highlighting the biochemical relationship between the two complicated diseases in the term of biochemical parameters vitamin D3, Calcium, Ferritin and iron. Thirty (30) patients suffers from both Alzheimer’s and type-2-diabetes participated in the present study, the study design involved two groups : the patients group included Alzheimer’s type-2-diabetic patients with the age ranged between (48-55) years and termed as (G) , this group compared with healthy subjects as a control group ( C ) which composed of thirty subjects matched in age with the patients. The biochemical parameters: HbA1c, FBS, vitamin D3, Calcium, Ferritin and Iron were determined in sera of the patients and control groups. It has been reported that the levels of HbA1c, FBS were highly significant increased while the levels of vitamin D3, calcium, ferritin and iron were highly significant decreased in sera of Alzheimer’s type 2- diabetic patients compared with the healthy subjects. The present study is the first in Iraq reporting that vitamin D3 deficiency is regarded as a risk factor to the low level of ferritin in Iraqi Alzheimer’s type-2- diabetic patients. Additionally, the biochemical parameters (vitamin D3, Calcium, Ferritin and iron) collectively submit a supportive finding to the bi-directional relationship between Alzheimer’s disease and type -2- diabetes mellitus.